Internalisasi Nilai Budaya Sipakatau dalam Akuntansi Pertanggungjawaban Sosial - Asriani Junaid; Edy Susanto; Muh. Arif; Muhammad Syafi'i A. Basalamah; Darwis Said (Politeknik Ganesha Medan, 2025)
Businesses play a significant role in addressing current environmental issues. Corporate Social Responsibility (CSR) represents a company’s commitment to economic (profit), social (people), and environmental (planet) principles. This study examines the implementation of social accountability accounting based on sipakatau values and CSR practices at PT Semen Bosowa Maros. Sipakatau, a core value of Bugis culture, emphasizes respect and recognition of others. As a societal norm, sipakatau serves as a behavioral guide, including in business practices. This study uses a qualitative method with an ethnomethodology approach, involving interviews, observations, and documentation. The findings reveal that sipakatau values are reflected in consultations (mappatabe) with local communities before making decisions that could impact their social and environmental systems. CSR practices at PT Semen Bosowa Maros not only benefit the company but also contribute to the sustainability of community life. CSR rooted in sipakatau fosters synergy between businesses, communities, and the environment. Support from both internal and external stakeholders is crucial for a company’s legitimacy. Therefore, sipakatau values are highly relevant and should be integrated as guiding principles in corporate social responsibility initiatives.